ELO2 Participates in the Regulation of Osmotic Stress Response by Modulating Nitric Oxide Accumulation in Arabidopsis - Zheng, Si-Qiu; Fu, Zheng-Wei; Lu, Ying-Tang (Frontiers in Plant Science, 2022)
The ELO family is involved in synthesizing very-long-chain fatty acids (VLCFAs) and VLCFAs play a crucial role in plant development, protein transport, and disease resistance, but the physiological function of plant ELO family is largely unknown. Further, while nitric oxide synthase (NOS)-like activity acts in various plant environmental responses by modulating NO accumulation, how the NOS-like activity is regulated in such different stress responses remains misty. Here, we report that a yeast mutant Δelo3 is defective in H2O2-triggered cell apoptosis with decreased NOS-like activity and NO accumulation, while its Arabidopsis homologous gene ELO2 could complement such defects in Δelo3. The expression of this gene is enhanced and required in plant osmotic stress response because the T-DNA insertion mutant elo2 is more sensitive to the stress than wild-type plants, and ELO2 expression could rescue the sensitivity phenotype of elo2. In addition, osmotic stress-promoted NOS-like activity and NO accumulation are significantly repressed in elo2, while exogenous application of NO donors can rescue this sensitivity of elo2 in terms of germination rate, fresh weight, chlorophyll content, and ion leakage. Furthermore, stress-responsive genes expression, proline accumulation, and catalase activity are also repressed in elo2 compared with wild type under osmotic stress. In conclusion, our study identifies ELO2 as a pivotal factor involved in plant osmotic stress response and reveals its role in regulating NOS-like activity and NO accumulation.